HEALTH LITERACY: AN OVERVIEW OF THE MEDICAL SECRETARIAL TRAINING IN TURKEY - Şenel Tekin, Perihan (International Journal of Research -GRANTHAALAYAH, 2018)
Background: Health literacy has a measure of capacity to access, understand, assess, and apply health information in individuals’ decision-making processes to maintain and improve life-quality quality of life. Research is a descriptive study aiming to determine the health literacy level of medical secretary’ students who are health professionals and the influencing factors of health literacy in the future. Method: The research was conducted between April 30 and June 1, 2018, and the study group consisted of 55 medical secretary students who study in Ankara University Vocational School of Health in Turkey. The participants were given the questionnaire which was composed of 3 sections (socio-demographic information, health status, and the Health Literacy Survey-European Union/HLS-EU scale) and 70 questions used for data collection purposes. Results: The average age of the group was 21.4±4.1. The average score of participants’ general health literacy index was calculated as 33.9±7.42 (n=55). Approximately 70% of participants (n=55) were found to have adequate health literacy. Conclusions: It is very important that the medical secretaries working as secretarial and patient orientation personnel in the health sector are health literate in terms of their own health and health service quality. Health literacy can’t be considered independent of the general literacy level. Hence, in the lifelong learning process, individuals need to be supported in school and work life.